Comparative Analysis of Factors Affecting the Underpricing Level of Sharia and Non Sharia Stocks at the time of Initial Public Offering - Lia Hidayah; Sunarsih Sunarsih (Journal of Islamic Economic Scholar, 2021)
Underpricing is a condition where the stock price of a company when conducting an Initial Public Offering (IPO) is below the stock price when it is on secondary market. In Indonesia, stocks are divided into two types, namely Sharia stock and non Sharia stock. This study aims to determine the effect of underwriter reputation, investment risk, profitability, financial laverage, and company size on the level of underpricing of Sharia stock and non Sharia stock. The sampling technique used was purposive sampling. The analytical method used is linear multiple regression with the type of cross section data. The results of the study found that there are differences that effect  the underpricing of Sharia stock and non Sharia stock. In Sharia stock, underpricing is only influenced by financial laverage, while in non Sharia stock underpricing is influenced by investment risk and company size. This study provides an overview to investors who have the aim of investing in companies that are IPOs for profit so that they carefully consider the influence of underwriter variables, investment risk, company size, financial laverage, and profitability. For companies, this research provides an overview to companies in order to make the right decisions in offering optimal stock prices. And for further researchers,